Memorias de un corpus bibliográfico para el estado del arte sobre la fundamentación de la intervención en trabajo social (2015)
ABSTRACT: This article presents the methodology used to conduct the research entitled “State of the art of the theoretical and methodological foundations of professional intervention in social work and the conceptualization of experiences in the Department of Antioquia, 1998-2008,” performed in four Latin American countries (Argentina, Chile, Brazil, and Colombia). Discourse analysis was used as a method to compile a bibliographic review which would lead to gathering and analyzing diverse and sufficient Latin American materials to fulfill the main purpose of this study: to evaluate the current state of production on the basis of professional intervention in social work. For this purpose, academic outreach material was defined as a written production published in books and journal articles, collecting results of thematic reflections, research reports, specialized dictionaries, edited memories of international seminars and conferences.